Crime and deviance in the colleges : elite student excess and sexual abuse - Punch, Maurice (Bristol University Press, 2022)
Timely and urgent, this book examines university culture regarding both sexual violence and excess in elite student societies. Taking a criminological and sociological perspective on the institutions, offenders and victims involved, the author recommends measures to improve crime prevention, accountability and the support for survivors.